Angiotensin-Converting Enzyme 2 Metabolizes and Partially Inactivates Pyr-Apelin-13 and Apelin-17: Physiological Effects in the Cardiovascular System. Issue 2 (August 2016) - Wang, Wang; McKinnie, Shaun M.K.; Farhan, Maikel; Paul, Manish; McDonald, Tyler; McLean, Brent; Llorens-Cortes, Catherine; Hazra, Saugata; Murray, Allan G.; Vederas, John C.; Oudit, Gavin Y.
Abstract : Apelin peptides mediate beneficial effects on the cardiovascular system and are being targeted as potential new drugs. However, apelin peptides have extremely short biological half-lives, and improved understanding of apelin peptide metabolism may lead to the discovery of biologically stable analogues with therapeutic potential. We examined the ability of angiotensin-converting enzyme 2 (ACE2) to cleave and inactivate pyr-apelin 13 and apelin 17, the dominant apelin peptides. Computer-assisted modeling shows a conserved binding of pyr-apelin 13 and apelin 17 to the ACE2 catalytic site. In ACE2 knockout mice, hypotensive action of pyr-apelin 13 and apelin 17 was potentiated, with a corresponding greater elevation in plasma apelin levels. Similarly, pharmacological inhibition of ACE2 potentiated the vasodepressor action of apelin peptides. Biochemical analysis confirmed that recombinant human ACE2 can cleave pyr-apelin 13 and apelin 17 efficiently, and apelin peptides are degraded slower in ACE2-deficient plasma. The biological relevance of ACE2-mediated proteolytic processing of apelin peptides was further supported by the reduced potency of pyr-apelin 12 and apelin 16 on the activation of signaling pathways and nitric oxide production from endothelial cells. Importantly, although pyr-apelin 13 and apelin 17 rescued contractile function in a myocardial ischemia–reperfusion model, ACE2 cleavage products, pyr-apelin 12 and 16, were devoid of these cardioprotective effects. We designed and synthesized active apelin analogues that were resistant to ACE2-mediated degradation, thereby confirming that stable apelin analogues can be designed as potential drugs. We conclude that ACE2 represents a major negative regulator of apelin action in the vasculature and heart. Abstract : Supplemental Digital Content is available in the text.